(untitled) - Thackeray, William Makepeace (Oxford, 1995)
Vanity Fair: A Novel without a Hero is a novel by William Makepeace Thackeray, first published in 1847-48, satirizing society in early 19th-century England. Vanity fair refers to a stop along the pilgrim's progress: a never-ending fair held in a town called Vanity, which is meant to represent man's sinful attachment to worldly things
Keywords: English language,English; Reading